Polański i symulacje. Na marginesie tekstu Ewy Mazierskiej "Roman Polański (i inni) przed sądem" - Izabela Tomczyk-Jarzyna (Załącznik Kulturoznawczy)
The text is a commentary on the article by Ewa Mazierska “Roman Polanski (and Others) on Trial.” Using Baudrillard’s concept of simulation, the author shows that discussions on Polanski’s personal conduct do not lead to finding meaning.